Lens-based Ka-band antenna system using planar feed - Silva, J. (2022)
This paper presents a simple, low-cost and compact mobile ground terminal antenna for Ka-band satellite communications that operates in the downlink band (19.7-20.2 GHz). The antenna is composed of a shaped dielectric lens which tilts in front of a planar feed to direct the beam. The planar feed is a circularly polarized patch antenna placed inside a cavity. The lens allows a mechanical beam steering from 0° to 57° in relation to zenith with a scan loss of 4.5 dB. In order to show the potential of a planar antenna as a feeder for this application, the proposed system is compared with a previous solution composed of the same dielectric lens and a horn antenna as feeder.